Understanding recent prices increases of animal-source foods in Myanmar - Minten, Bart; Aung, Nilar; Aung, Zin Wai; Htar, May Thet (International Food Policy Research Institute, 2025)
The livestock sector in Myanmar represents a significant component of the national economy, contributing approximately 6 percent to the country’s GDP. Beyond its economic role, the sector provides critical livelihood opportunities for rural households and underpins the supply of animal-source foods (ASF), which are essential for enhancing dietary diversity and nutritional outcomes. A resilient and efficiently functioning livestock sector also generates important multiplier effects, contributing to poverty reduction, employment creation, and overall economic growth (Diao et al. 2024). This note summarizes recent structural and market developments in Myanmar’s livestock industry and examines their implications for ASF price dynamics.